(untitled) (Fountain Journal of Natural and Applied Sciences, 2016)
There has been a great increase in the use of wireless networks over the years; Mobile Ad hoc Network is an example of such wireless network. It functions without any central administration and the network is made up of a collection of nodes within a radio frequency. Security in mobile network has been an area of great research over the years mainly because most ad hoc protocols do not provide the basic security framework and services. This paper aims at simulating access control in wireless ad-hoc networks. The objectives are to ensure that the network is not vulnerable and should also devoid of any form of malicious attack that could prevent authorized access. Two metrics (packet delivery ratio and traffic overhead) were used to measure the effectiveness and efficiency of the networks. Through a detailed simulation study, we show that the protocol is efficient and allows a trade-off between security and performance. This research focuses on designing an access control mechanism that was incorporated within ad-hoc routing protocols with the aim of adding an extra layer of security against threats in the network. The three stage-process for access control was implemented with NS-2 v 35. The nodes in the simulation were created dynamically, the movement between nodes was generated randomly and the connections between the nodes were done using Constant Bit Rate (CBR) connection which was aimed at enabling the network to mimic a real life scenario. Through different experiments and simulations done, it was observed that the access control model works and also provides a higher level of security for ad-hoc networks even when under security threats and attacks. Keywords: Access control, NS 2, Ad-Hoc, MANET, Mobile, Simulation.